Mozambique - Beating the Odds : Sustaining Inclusion in a Growing Economy - A Mozambique Poverty, Gender, and Social Assessment, Volume 1. Main Report - World Bank (Washington, DC, 2012)
This assessment, reflecting poverty's many dimensions in Mozambique, combines multiple disciplines and diagnostic tools to explore poverty. It combines quantitative and qualitative approaches to understand trends in poverty and the dynamics that shape them. The objective is to support the development and implementation of proper policies that really work by taking poverty's multiple dimensions into account. The first analysis is using multiple quantitative and qualitative indicators on levels and changes in the opportunities and outcomes for households and communities in Mozambique since 1997. The main economic developments, analyzes how changes at the macro and meson level affected household livelihoods, and how households, especially poor households, responded. Agriculture and the private sector, especially labor-intensive activities, many of them small and informal. It can build human capital by improving access to basic public services, especially for the poor, and by increasing the value for money in public spending. And it can improve governance and accountability by getting government closer to its citizens. To achieve these goals, the government will need to increase the value for money in its spending on public services. It will also need to target services for the rural poor and enlist poor communities in identifying needs and delivering those services. And it will need to put in place good tracking systems to link program outputs to targets and outcomes, using frequent high-quality household surveys. Mozambique was an extremely poor country at the time of its elections in 1994, with decimated infrastructure, a weak economy, and fragile institutions. Since then, it has been astonishingly successful at restoring growth and improving welfare. Sustained growth -- driven primarily by investments in physical capital -- reduced monetary poverty from 69 percent of the populace in 1997 to 54 percent in 2003 and the depth and severity of no income poverty even more. Broad-based, labor-intensive private-sector growth was efficient in reducing poverty until 2003 because it was equally distributed. At the same time, investments in social and economic infrastructure extended access to public services, reduced welfare inequalities, and supported the livelihoods of the average Mozambican.